Talk sense to yourself : a program for children and adolescents - Wragg, Jeffrey (Hawthorn, Vic. : Australian Council for Educational Research, 1989)
This book is about: Disruption in schools; Use of the Programs in a School or Clinical Setting; Talk Sense to Yourself Program; ...
Keywords: Education; Teaching; Behaviour modification; Behaviour modification; Self-control in children -- Study and teaching; Problem children -- Education